1990
DOI: 10.1111/j.1365-2621.1990.tb05251.x
|View full text |Cite
|
Sign up to set email alerts
|

Thiamin Retention and Other Characteristics of Cooked Beef Loin Roasts

Abstract: Beef loin roasts were prepared by three procedures that simulated home, foodservice or commercial methods for precooking meat prior to vacuum packaging. Roasts were prepared by conventional electric (176.5"C), cook-in-package waterbath (70°C water), or smokehouse (ambient temperature) heating. Yield, thiamin, fat, water content, and Instron tenderness of roasts were determined. Raw roasts had higher (P ~0.05) water and free water content. All cooked roasts were significantly lower in thiamin content (dry, fat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
2

Year Published

1993
1993
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 5 publications
1
5
0
2
Order By: Relevance
“…Masˇkova´et al (1994) observed the retention of thiamin in the range of 20-85% during culinary treatment of meat. Their results are in line with those of Cooksey et al (1990) observed during roasting. Results of thiamin losses in chicken meat are in line with those of Hall and Lin (1981), Barbeau and Schnepf (1989), and Ang et al (1978), in contrast to Al-Khalifa and Dawood (1993), who observed a retention of thiamin of only 45% during roasting.…”
Section: Thiaminsupporting
confidence: 94%
“…Masˇkova´et al (1994) observed the retention of thiamin in the range of 20-85% during culinary treatment of meat. Their results are in line with those of Cooksey et al (1990) observed during roasting. Results of thiamin losses in chicken meat are in line with those of Hall and Lin (1981), Barbeau and Schnepf (1989), and Ang et al (1978), in contrast to Al-Khalifa and Dawood (1993), who observed a retention of thiamin of only 45% during roasting.…”
Section: Thiaminsupporting
confidence: 94%
“…Besides amino acid composition, thiamine content is a crucial index of meat and meat product nutritive value. Previous studies showed that thermal processing causes great thiamine losses [Cooksey et al 1990, Szymandera-Buszka and Waszkowiak 2003, Seidler et al 2004, Szymandera-Buszka et al 2006, Szymandera-Buszka 2012. Moreover, products of lipid oxidation intensify the unfavourable heat effect to thiamine [Szymandera-Buszka 2003].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, few publications dealt with the storage stability of these products (Church & Parsons, 1993; Hansen et al ., 1995). However, a number of investigations about technological characteristics, sensory quality and shelf‐life stability of s ous vide and vacuum cook‐in bag meat have been published (Buck et al ., 1979; Dinardo et al ., 1984; Smith & Alvarez, 1988; Stites et al ., 1989; Cooksey et al ., 1990; Hansen et al ., 1995; Bertelsen & Juncher, 1996; Church, 1996; Thorsell, 1996; Palka & Daun, 1999; Vaudagna et al ., 1999; Church & Parsons, 2000).…”
Section: Introductionmentioning
confidence: 99%